Environmental Risk Analysis for Asian-Oriented, Risk-Based Watershed Management Japan and Malaysia (Springer Singapore, 2018)
This publication is a practical guidebook on environmental risk assessment, especially for watershed-scale management. It highlights case studies of watershed environmental risk in Malaysia, including the potential health risks as well as screening methods and management in practice. In order to apply environmental risk assessment methods for the management of toxic chemicals, it is necessary to consider the geological and climate features of each country as well as their cultural characteristics. Focusing on Malaysia as a representative country, the book also discusses studies in other Asian countries. The insights provided can be applied to advanced and developing countries alike. A suitable textbook for graduate students, it is also a valuable reference source for researchers, practitioners and policymakers.